Btk Inhibitors as First Oral Atherothrombosis-Selective Antiplatelet Drugs? - Busygina, Kristina; Denzinger, Viola; Bernlochner, Isabell; Weber, Christian; Lorenz, Reinhard; Siess, Wolfgang (Thrombosis and Haemostasis, 2019)
Bruton's tyrosine kinase (Btk) is essential for B cell differentiation and proliferation, but also platelets express Btk. Patients with X-linked agammaglobulinemia due to hereditary Btk deficiency do not show bleeding, but a mild bleeding tendency is observed in high dose therapy of B-cell malignancies with ibrutinib and novel second-generation irreversible Btk inhibitors (acalabrutinib and ONO/GS-4059). This review discusses recent studies that may explain this apparent paradox and gives mechanistic insights that suggest a unique potential of low dose irreversible Btk inhibitors as atherothrombosis-focused antiplatelet drugs.
Keywords: Btk inhibitor; platelet; bleeding; GPVI; GPIb; X-linked agammaglobulinemia